Global Climate Change and Aspects of Regional Climate Change in the Berlin-Brandenburg Region - Cubasch, Ulrich; Kadow, Christopher (DIE ERDE – Journal of the Geographical Society of Berlin, 2011)
To obtain an estimate of the average temperature of the northern hemisphere during the last 1200 years, proxy data have been merged with instrumental recordings. These instrumental measurements are, with a few exceptions, only available for the recent 150 years. In the city of Berlin the temperature has been recorded since as early as 1701. However, during the first 150 years the measurements were problematic as location, measurement procedure and instruments changed frequently and without proper documentation. From 1847 onwards observations became more reliable once the Royal Prussian Meteorological Institute had been established. For the last 100 years temperature and precipitation measurements have been performed in parallel at Berlin-Dahlem and Potsdam. The datasets recorded in the city of Berlin and in Berlin-Dahlem have been merged to obtain a record of more than 300 years. It indicates that the temperature of Berlin has risen by 1.04°C during the last 100 years after correcting for the urbanisation effect. In the same period, the total number of frost days has significantly decreased by almost 17 days, and the number of summer days has significantly increased by about 12 days. Annual mean precipitation has hardly changed (decrease less than 0.2 %) during the last century. However, rainfall has decreased by about 4 % in summer and increased by 3 % in winter. All precipitation changes are below the 95 % significance level. Model projections indicate that warming will continue which means that Berlin-Brandenburg will experience a temperature rise of about 3-3.5°C by the end of this century for the IPCC scenario A1B. For the same scenario precipitation is expected to increase by 10-20 % in winter and to decrease by 10-30 % in summer: The seasonal precipitation changes compensate each other resulting in an almost unchanged annual mean.